Root Membrane Replantation as an Alternative Technique for the Socket Preservation. (2nd May 2022) - Campione, Francesco; Campione, Ludovica; Campione, Mario Francesco; Melillo, Michele; Arena, Claudia; Abella, Francesc; Boschini, Luca
Abstract : Background and Overview . Socket shield is a technique that allows the maintenance of tissue volumes. In the reported clinical case, the replantation of the buccal root fragment mistakenly extracted during a socket shield surgery is performed. We present a follow-up to 5 years with an unexpected healing. Case Description . An 88-year-old patient underwent an immediate loading implant placement associated with the replantation of the mistakenly extracted root fragment. The shaping of the fragment was performed extraorally, and the replantation was done so that the fragment protruded above the crest margin. Conclusions and Practical Implications . The 5-year follow-up shows an uneventful healing of the implant. At 48 months, postoperative CBCT exam reports images compatible with the regeneration of the bone over the portion of root that protruded over the margin. The outcome suggests clinical implications, as the opportunity to easily shape the fragment extraorally and replant sound portion of the root (not necessary the buccal) in buccal socket with bone defect.